Qualitative Researches: Curriculum Integrity and Product Richness - Mustafa, Adnan Yassin (ALBAHITH ALALAMI, 2020)
These researches have shown the magnitude of the influence that culture exerts on all human extensions and spaces. Rather, the conviction of many thinkers, researchers and specialists in the comprehensiveness of this influence is such that it is used as a starting point and perspective to explain the various aspects, manifestations, problems and practices. According to these perceptions, a man carries a cultural mind that is slowly formed throughout the young years of a man’s life and is completed upon reaching the age of maturity. Therefore, it has become evident in the behavioral, social and human sciences to acknowledge the multiplicity of human thought patterns as a natural result of the different cultures of peoples and societies. From here comes the broad academic recognition of the relationship of personality structure to the historical and social pattern of culture. Based on these data and perceptions, it is difficult to understand the relationships of people and the behavior of individuals unless we analyze those relationships and behavior within the framework of the values and cognitive concepts prevailing in society. Here, qualitative researches leave their mark and become more important to explore many social scenes, behavioral practices and societal phenomena